What is the algebraic expression in 11x-6x-x

Question

What is the algebraic expression in 11x-6x-x

in progress 0
Piper 2 hours 2021-09-13T06:18:42+00:00 2 Answers 0

Answers ( )

    0
    2021-09-13T06:20:03+00:00

    Answer:

    4x

    Step-by-step explanation:

    Simplify. Combine like terms. Note that x = 1x, being that there is one variable of x.

    11x – 6x = 5x

    5x – x = 4x

    4x is your answer.

    ~

    0
    2021-09-13T06:20:15+00:00

    Answer:

    4x

    Step-by-step explanation:  


    Simplify. Combine like terms. Note that x = 1x, being that there is one variable of x.  

    11x – 6x = 5x

    5x – x = 4x

    4x  answer.

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )